2005
DOI: 10.1161/01.cir.0000152101.41037.ab
|View full text |Cite
|
Sign up to set email alerts
|

KRP-203, a Novel Synthetic Immunosuppressant, Prolongs Graft Survival and Attenuates Chronic Rejection in Rat Skin and Heart Allografts

Abstract: Background-A novel immunomodulator, KRP-203, the molecular structure of which has some similarity to FTY720, has been developed for use in organ transplantation. The present study was designed to investigate the potency and safety of KRP-203 on allograft survival against both acute and chronic rejection in rat skin and heart transplantation. Methods and Results-KRP-203 significantly prolonged skin or heart allograft survival of a minor histocompatibility complex (mHC)-disparate (LEW to F344) rat combination. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
83
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 19 publications
7
83
0
1
Order By: Relevance
“…The success of FTY720 in the clinic has spurred the search for similar molecules, particularly with S1P 3 -sparing activity. FTY720-like prodrugs include 2-ammonio-4-(2-chloro-4-(3-phenoxyphenylthio)phenyl)-2-(hydroxymethyl)butyl hydrogen phosphate (KRP-203) (Shimizu et al, 2005) and 1-[1-amino-3-(4-octylphenyl)cyclopentyl]methanol (VPC01091) (Zhu et al, 2007) and are, after phosphorylation, agonists for S1P 1 , S1P 4 , and S1P 5 but not S1P 2 or S1P 3 . Numerous compounds that target S1P 1 and S1P 5 as direct agonists have been described previously (Li et al, 2005); most of these remain visible only in the patent literature.…”
Section: B Sphingosine 1-phosphate Receptor Compoundsmentioning
confidence: 99%
“…The success of FTY720 in the clinic has spurred the search for similar molecules, particularly with S1P 3 -sparing activity. FTY720-like prodrugs include 2-ammonio-4-(2-chloro-4-(3-phenoxyphenylthio)phenyl)-2-(hydroxymethyl)butyl hydrogen phosphate (KRP-203) (Shimizu et al, 2005) and 1-[1-amino-3-(4-octylphenyl)cyclopentyl]methanol (VPC01091) (Zhu et al, 2007) and are, after phosphorylation, agonists for S1P 1 , S1P 4 , and S1P 5 but not S1P 2 or S1P 3 . Numerous compounds that target S1P 1 and S1P 5 as direct agonists have been described previously (Li et al, 2005); most of these remain visible only in the patent literature.…”
Section: B Sphingosine 1-phosphate Receptor Compoundsmentioning
confidence: 99%
“…1). Furthermore, Shimizu et al (2005) have reported that KRP prolonged graft survival and attenuated chronic rejection in rat allograft models, which suggests that KRP regulates not only T cell response but also B cell response. In our previous report, however, FTY did not affect the number of B cells (Mizushima et al, 2004).…”
mentioning
confidence: 98%
“…18,19 In addition, several other S1P 1 selective agonists have been reported to have similar therapeutic potential. 20,21 On the other hand, compelling evidence suggests S1P 1 agonists can also exert their function by tightening the stromal portal of the lymph node, therefore restricting lymphocyte efflux. 22 These different opinions of the mechanism underlining the function of existing S1P 1 agonists warrant the need for thorough understanding of the relationship of desired in vivo activity and potencies in different in vitro assays.…”
Section: Introductionmentioning
confidence: 99%